PENGARUH UKURAN PERUSAHAAN, LEVERAGE, DAN PROFITABILITAS TERHADAP MANAJEMEN LABA - Via Nur Kharomah (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2022)
This study aims to find out how the variables of Firm Size, Leverage, and Profitability affect  Earning Management in Mining Industry companies listed on the Indonesia Stock Exchange  for the period 2014-2018. The sample data used were 17 mining industry companies. The  method of data analysis was carried out by the method of multiple linear regression analysis  with the help of the SPSS version 22.0 application. The results of this study indicate that firm  size has a significant negative effect on earnings management, leverage has an insignificant  negative effect on earnings management, and profitability has a significant positive effect on  earnings management.